Integration of hydrogeophysics and remote sensing with coupled hydrological models - Francés, Alain Pascal (2015)
Dissertation to obtain the degree of doctor at the University of Twente, on the authority of the rector magnificus, prof. dr. H. Brinksma, on account of the decision of the graduation committee, to be publicity defended on Friday, July 17, 2015 at 14:45 hrs